Ralstonia solanacearum decreases volumetric growth of trees and yield of kraft cellulose of Eucalyptus spp. Issue 1 (19th August 2017) - Ferreira, M. A.; Mafia, R. G.; Alfenas, A. C.
Summary: Ralstonia solanacearum is currently one of the most important plant pathogenic bacteria worldwide, with a wide geographical distribution and host diversity. The pathogen infects more than 200 plant species belonging to approximately 50 plant families, including Eucalyptus spp. Although, high losses have been reported in nurseries, little is known on the negative impact of the disease in the field. In this study, we evaluated the incidence of R. solanacearum and its effect on volumetric growth and cellulose yield of discoloured wood chips obtained from infected trees of one clone of Eucalyptus urophylla and two hybrid clones of Eucalyptus urophylla  ×  E. grandis . The average incidence of bacterial wilt ranged between 60.6% and 72.4%. Volumetric growth of infected trees disease decreased 78.6% and 81.7% at 18 and 30 months, respectively. The pulp screen yield of three clones decreased between 3.2 and 6.4%, with an average 4.3%. The results of this work provide useful information on the losses of volumetric growth and pulp yield of eucalypt caused by R. solanacearum .